“Una resolución, luchar hast’al fin!”: a experiência da Guerra Civil Espanhola nos escritos de George Orwell - Costa, Carolina da Purificação (2013)
This paper has for object analyze the experience of the Spanish Civil War (1936-1937) through the writings of English George Orwell, seeking to understand, in their comprehension about the event, the gaze that their condition of foreigner printed to the conflict and the modifications that the reality of the front has made in the vision that he had about his own country, England. For this reason, this study aimed to examine their previous experiences the War with the objective of characterizing their worldview forged in accord with their identity; and consider its performance writing after the confrontation in an attempt to grasp the depth of the modification effected by experience during his stay in Spain, understanding it within a context of dispute of memories.